A cross-country analysis of the roles of border openness, human capital and legal institutions in explaining economic development. Issue 1 (2nd January 2022) - Oyèkọ́lá, Ọláyínká
Abstract : Globalisation, human capital, and institutions have been widely recognised in the literature to be causally important for economic development. Most of the available studies, however, treat measures of these determinants either separately or as substitutes. In this paper, we study the income effects of border openness to migration, education, and the rule of law (our proxies for globalisation, human capital, and institutions, respectively). Using cross-country data covering all regions of the world, and employing instrumental variables for all three factors, we establish that they each have a robust, positive, and strong association with economic development. We then consider whether there are any useful interrelations between the three factors in explaining income. On the interaction effects, the results show that the impact on income of: (i) migration can be materially affected by cultivating good institutions but this effect is not dependent on the education level; (ii) education is important irrespective of the levels of migration and institutions; and (iii) institutions is significantly improved by raising the level of education but is not influenced by migration level. Our paper makes a significant contribution as the first investigation into the effects of migration, education, and institutions jointly and as complements.